The prevalence of Hemophilia A in males in Africa: evidence from a systematic review and meta-analysis - Mitiku Bonsa Debela; Kebebe Bekele; Demisu Zenbaba (BMC, 2024)
Abstract Background Hemophilia A (HA) is an X-linked recessive bleeding disorder characterized by reduced or absent coagulation factor (F) VIII activity. The empirical evidence on the prevalence of HA in Africa has reported inconsistent findings and seems to present such a wide range of prevalence that it is hard to swiftly ascertain its average extent. Hence, this review aimed to pool the results of primary studies reporting the prevalence of HA into a single estimate in the region. Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles published in EMBASE, PubMed, Web of Science, SCOPUS, Science Direct, and Cochrane Library databases were searched. Observational studies revealing the prevalence of HA in Africa between 2010 and 2023 were incorporated. We assessed the quality of each study using the Newcastle-Ottawa quality assessment tool. The prevalence of HA was estimated as the cases (the sample size) per 100,000 population multiplied by 1000. To produce the pooled estimate, Der Simonian random-effects models were computed with Metaprop on the STATA command. The studies' heterogeneity was assessed using the I-squared (I2) value test and the Galbraith plot. A funnel plot was conducted to evaluate publication bias. Results Of the 337 studies accessed, we included 15 that fulfilled the eligibility criteria. The random-effect model meta-analysis demonstrated the overall pooled prevalence of HA was 6.82 cases per 100,000 persons (95% confidence interval: 5.16, 8.48) with heterogeneity (I2 = 0.00%, p < 0.001). Conclusions This systematic review and meta-analysis revealed that HA is an alarming problem that may pose a future threat to public health in Africa. Given the detrimental effects of the disease on health and the complications involved, we recommended that African regions increase patient access to factor VIII medication, improve carrier detection rates, and take the initiative toward the development and access to gene therapy.